REGENERATION OF DENTAL TISSUES USING BIOCOMPOSITE MATERIALS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The regeneration of dental tissues represents a rapidly advancing field in modern dentistry, driven by the growing demand for biologically compatible and long-lasting restorative solutions. Biocomposite materials, which combine natural and synthetic components, have emerged as promising candidates for dental tissue regeneration due to their favorable mechanical properties, biocompatibility, and ability to support cellular activity.